TÁLIM HÁM TÁRBIYA TÚSINIKLERI HÁM ONÍŃ QATNASÍWSHÍLARÍN SOCIALLÍQ QORǴAW - Qayratdinova, U. (SCIENCE and SOCIETY, 2022)
The article examines the social protection of the rights of participants in education, the work carried out in the Republic of Uzbekistan to protect their rights, and the issued regulatory legal acts.